ANALISIS RISIKO LIKUIDITAS BANK SYARIAH DENGAN METODE STOCK BASED DAN FLOW BASED - Yahya, Amir; Sitasari, Ita; Syuhada, Sonia; Saprudin, Saprudin (Journal of Information System, Applied, Management, Accounting and Research, 2026)
This study aims to analyze the potential liquidity risk of Islamic commercial banks classified under BUKU 1, namely Bank Victoria Syariah (BVS) and Bank Jabar Banten Syariah (BJBS), which have core capital below IDR 3 trillion during the 2019–2021 period. The research adopts a quantitative approach with descriptive analysis, utilizing secondary data obtained from the annual financial statements of both banks. Liquidity risk is assessed using stock-based and flow-based measurement methods. The results of the stock-based analysis indicate that, based on the ratio of liquid assets to short-term liabilities, both banks are categorized as having low liquidity risk. However, when measured using the ratio of liquid assets to total assets, the liquidity risk is classified as moderate, suggesting that both banks remain in a stable financial condition. The Financing to Deposit Ratio (FDR) also shows values within a normal range. Meanwhile, flow-based analysis reveals a negative liquidity gap in the short-term maturity period of less than three months, indicating potential short-term liquidity pressure.